Triple salting-out effect: a required phenomenon in the formation of ionic-liquid-based aqueous multiphase systems - Passos, Helena (Angew Chem Int Ed Engl, 2017)
Novel aqueous multiphase systems (MuPS) formed by quaternary mixtures composed of cholinium-based ionic liquids (ILs), polymers, inorganic salts and water are here reported. The influence of several ILs was studied, demonstrating that a triple salting-out is a required phenomenon to prepare MuPS. The respective phase diagrams and “tie-surfaces” were determined, followed by the evaluation of the effect of temperature. Finally, it is shown the remarkable ability of IL-based MuPS to selectively separate a complex mixture of dyes.